An Effect Of Occupational Safety And Health On Employee Performance At PT. PLN (Persero) ULP Binjai Barat - Risman Setiawan; Yohny Anwar; Henry Aspan (Britain International for Academic Research (BIAR) Publisher, 2022)
This study aims to test and analyze the effect ofoccupationalsafety (X1) andhealth(X2) on the performance (Y) of employees at PT. PLN (Persero) Customer Service Unit of West Binjai. The data analysis technique used in this study is descriptive quantitative, with the number of samples are 50 respondents. The analysis used is statistical data analysis using namely multiple linear regression analysis and hypothesis testing. The result of this study shows that world safety (X1) partially has a positive and significant effect on the performance of employees at PT. PLN (Persero) Customer Service Unit of West Binjai. Likewise, the health (X2) partially has positive and significant effect on the performance of employees at PT. PLN (Persero) Customer Service Unit of West Binjai. then, the simultaneous testing of the variables in this study consisting of occupational safety and health have a positive and significant effect on the dependent variable which is the performance of employees at PT. PLN (Persero) Customer Service Unit of West Binjai.